2015
DOI: 10.1002/ps.3987
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring bioactive compounds from four repellent essential oils against Bemisia tabaci whiteflies

Abstract: This new sustainable strategy for protecting vegetable crops against whiteflies is discussed, in addition to the use of companion plants that could produce such bioactive compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 56 publications
2
44
0
2
Order By: Relevance
“…It has insecticidal properties (Ryan and Byrne 1988;Weaver et al 1991) and as the main component in the headspace of ripe peach fruit (Park et al 2005;ElSayed et al 2014), it is repellent to aphids, mites, and thrips (Koschier et al 2007;Ulland et al 2008;Mallinger et al 2011), Aedes aegypti (Linnaeus), the mosquito vector of Dengue (Dekker et al 2011) and the whitefly Bemisia tabaci (Gennadius) (Delétré et al 2015). It is also an effective pesticide for the control of ticks, fleas, and the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has insecticidal properties (Ryan and Byrne 1988;Weaver et al 1991) and as the main component in the headspace of ripe peach fruit (Park et al 2005;ElSayed et al 2014), it is repellent to aphids, mites, and thrips (Koschier et al 2007;Ulland et al 2008;Mallinger et al 2011), Aedes aegypti (Linnaeus), the mosquito vector of Dengue (Dekker et al 2011) and the whitefly Bemisia tabaci (Gennadius) (Delétré et al 2015). It is also an effective pesticide for the control of ticks, fleas, and the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Companion crops could be identified from these plants to potentially aid in the recruitment of the predatory mite family Phytoseiidae against target tetranychid mites in several solanaceous crop systems, including tomatoes. In their study on the repellent properties of plant extracts, Delétré et al (2015) showed that coriander Coriandrum sativum (Linnaeus) essentially containing linalool (72 %) had repellent properties against the whitefly B. tabaci a major pest of tomato. The use of coriander as a companion plant could have a double benefit effect of repelling pest B. tabaci and attraction of predatory mites.…”
Section: Discussionmentioning
confidence: 99%
“…tabaci adults on tomato. Deletre et al [35] reported that geraniol and citronellol posessed repellent, irritant and toxic activities, depending on their applied concentrations, and those activities were independent for both compounds. Hence, could be used in coating nets for repellent activities in nethouses.…”
Section: Introductionmentioning
confidence: 99%
“…These organic volatile compounds are well known for their insecticidal, antifeedant, repellent, attractant and oviposition deterrent effects on insect pests [25,26]. For instance, aromatic basil (Ocimum basilicum) was found to offer repellent action against mosquitoes [27] and flea beetles on Pechay (Brassica perkinensis) [28].…”
Section: Introductionmentioning
confidence: 99%